Thyroid function, renal function, and depression: an association study - Liang, Hai; Wang, Jin-min; Wei, Xiao-qian; Su, Xiao-qin; Zhang, Bi-xia (Frontiers in Psychiatry, 2023)
Objective To investigate the correlations between thyroid function, renal function, and depression. Methods Clinical data of 67 patients with Major depressive disorder (MDD) and 36 healthy control subjects between 2018 and 2021 were collected to compare thyroid and renal function. Thyroid and renal functions of depressed patients were then correlated with the Hamilton Depression Rating Scale (HAMD) and the Hamilton Anxiety Rating Scale (HAMA).Spearman correlation analysis was used to find the correlation between renal function, thyroid function, and depression. A logistic regression was performed to find significant predictors of depression. Results Triiodothyronine protamine (T3), thyroxine (T4), free triiodothyronine protamine (FT3), uric acid, sodium, and anion gap were lower in the MDD group than in the control group (p < 0.05). Correlation analysis of thyroid function, renal function, and factor terms of HAMD in the MDD group suggested that diurnal variation, hopelessness, and depression level were positively correlated with thyrotropin (TSH) (p < 0.05). Cognitive disturbance, retardation, and depression level were negatively correlated with creatinine (p < 0.05). Diurnal variation was negatively correlated with sodium ion (p < 0.01); hopelessness and depression level were positively correlated with chloride ion (p < 0.05); diurnal variation, retardation, and depression level were negatively correlated with anion gap (p < 0.05). Diurnal variation (p < 0.01) and retardation (p < 0.05) were negatively correlated with osmolality. Cognitive disturbance and depression level were positively correlated with estimated glomerular filtration rate (eGFR) (p < 0.05). In the MDD group, correlation analysis of thyroid function, renal function, and HAMA factor terms suggested that the total HAMA score and anxiety level were positively correlated with chloride ion (p < 0.05); psychic anxiety, total HAMA score, and anxiety level were negatively correlated with anion gap (p < 0.05). Furthermore, a low level of anion gap was an independent risk factor for depression and anxiety levels (p < 0.05). Conclusion Low thyroid function and reduced waste metabolized by the kidneys in patients with MDD suggest a low intake and low metabolism in depressed patients. In addition, subtle fluctuations in the anion gap in depressed patients were strongly correlated with the degree of depression and anxiety.